The Impact of Inequality on the Informal Economy in Latin America and the Caribbean with a MIMIC Model - Marcos Takanohashi; Marcel Ribeiro; Friedrich Schneider (Center for Economic Studies and ifo Institute (CESifo), 2023)
Vast literature is available covering main Informal Economy (IE) causes and consequences for Latin America and Caribbean (LAC), but its size estimation has been mainly limited to worldwide models applied to the region. This paper proposes a MIMIC Base Model using a data set composed by 41 countries in LAC, in which both inequality and total factor productivity are introduced on top of traditional variables. Modelling results on IE estimates for LAC countries that are at par with the literature. When compared with a model using data from 188 countries, inequality has an impact ten-fold higher in the level of informality. Results suggest the importance of tailored data set selection when modelling IE with MIMIC.
Keywords: D78; E26; H26; H32; O17; O54; 330; Informal Economy (IE). MIMIC (Multiple Indicators Multiple Causes); shadow economy; underground economy; non-observed economy; inequality; informality; tax burden; quality of state institutions; regulations; governance; GINI coefficient; TFP; Latin America and Caribbean (LAC)